2005
DOI: 10.2134/jeq2004.0428
|View full text |Cite|
|
Sign up to set email alerts
|

The Acetochlor Registration Partnership: Prospective Ground Water Monitoring Program

Abstract: The Acetochlor Registration Partnership conducted a prospective ground water (PGW) monitoring program to investigate acetochlor [2-chloro-N-(ethoxymethyl)-N-(2-ethyl-6-methylphenyl)-acetamide] transport to ground water at eight sites. The distribution of soil textures among these sites was weighted toward coarser soil types, while also including finer-textured soils that dominate most corn (Zea mays L.)-growing areas of the United States. Each site consisted of a 1.2-ha test plot adjacent to a 0.2-ha control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This is not surprising given that subsequent site‐specific investigations revealed that these sites, like others among the 14 with detections, were subject to direct interactions between ponded runoff water and the well. PRZM is unable to cope with either this process or preferential flow, the latter of which has been implicated in the only PGW (Prospective Ground Water Monitoring study) where parent acetochlor was detected, albeit only at trace (<0.10 μg L −1 ) levels, in shallow ground water (Newcombe et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising given that subsequent site‐specific investigations revealed that these sites, like others among the 14 with detections, were subject to direct interactions between ponded runoff water and the well. PRZM is unable to cope with either this process or preferential flow, the latter of which has been implicated in the only PGW (Prospective Ground Water Monitoring study) where parent acetochlor was detected, albeit only at trace (<0.10 μg L −1 ) levels, in shallow ground water (Newcombe et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This publication describes the methods, results, and interpretation of the GWM. The ARP's surface water monitoring program and the field leaching studies are described in companion publications (Hackett et al, 2005; Newcombe et al, 2005).…”
mentioning
confidence: 99%
“…Values of DT50 for surface horizons obtained in the present study are greater than those measured in the field. For example, Mueller et al reported a DT50 value of 6.3 d for the upper 8 cm of a soil, Ma et al reported a value of 9 d for the top 10 cm of 2 soils, and Newcombe et al reported 3 to 9 d for the top 15 cm of soil depth. Similarly, Taylor et al reported laboratory‐determined DT50 values of approximately 9, 12, and 13 d for depth ranges of between 0 and 30 cm, 100 and 130 cm, and 270 and 300 cm, which suggest no clear effect of depth on DT50, something that was also observed by Vaughan et al and Dictor et al .…”
Section: Resultsmentioning
confidence: 99%
“…This paper presents the methods, results, and interpretation of the acetochlor surface water monitoring program. Two distinct acetochlor ground water monitoring programs are described in companion publications (de Guzman et al, 2005; Newcombe et al, 2005). We begin with the methods used, focusing on site selection and sampling logistics.…”
Section: Acetanilide Herbicides and Their Degradates Included In The mentioning
confidence: 99%